Gadolinium-Enhanced CT Angiography of the Circle of Willis and Neck - Henson, John W.; Nogueira, Raul G.; Covarrubias, Diego J.; Gonzalez, R. Gilberto; Lev, Michael H. (American Journal of Neuroradiology, 2004)
Summary: CT angiography (CTA) of the cervical and intracranial vessels is a rapid, noninvasive, and relatively inexpensive technique for the evaluation of vascular abnormalities. Contraindications to the use of contrast media, however, can preclude use of iodinated agents for CTA. We report the use of gadolinium as contrast agent for CTA of the head and neck in three patients with contraindications to iodinated contrast agents.